Synthesis of Hydrophobic Propionyl Neohesperidin Ester Using an Immobilied Enzyme and Description of Its Anti-proliferative and Pro-apoptotic Effects on MCF-7 Human Breast Cancer Cells - Xia, Na; Wan, Wenjing; Zhu, Siming; Liu, Qiang (Frontiers in Bioengineering and Biotechnology, 2020)
Neohesperidin (NH) is a natural flavonoid glycoside compound with considerable physiological and pharmacological activities. However, its bioavailability is limited due to poor solubility, and few studies have so far attempted improve the solubility and bioavailability of NH. In this study, we structurally modified NH using an immobilised lipase to improve lipophilicity and therefore expand its applicability in lipophilic media as well as enhance its bioavailability in vivo. In addition, we aimed investigated the pro-apoptoptotic activity of this new compound (propionyl neohesperidin esther, PHNE) in MCF-7 breast cancer cells using a variety of cellular assays, including the MTT (3-(4, 5-dimethyl- 2-thiazolyl)-2, 5-diphenyl-2-h-tetrazolium bromide assay, assessment of intracellular reactive oxygen species (ROS) levels, and flow cytometry. We successfully synthesised PNHE using immobilised lipases, and the esterification of NH was confirmed by Fourier transform-infrared spectroscopy (FT-IR). Compared to NH, HNPE showed higher anti-proliferative and pro-apoptotic in MCF-7 breast cancer cells, which may be explained by its increased lipophilicity compared to neohesperidin, benefiting to the action of NH on the cancer cell wall .The IC50 of PNHE for inducing apoptosis of MCF-7 cells was 185.52 μg/mL. PNHE increased both the proportion of cells in Sub-G1 phase and the cellular ROS content, suggesting that HNPE could be a potential candidate for the treatment of breast cancer.